2016
DOI: 10.1186/s12876-016-0500-x
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate inhibits interleukin-17 and generates Tregs to ameliorate colorectal colitis in rats

Abstract: BackgroundButyrate is an energy source for colonocytes that is formed by bacterial fermentation of dietary fiber in the colon and that exerts broad anti-inflammatory activities. Although the administration of butyrate improves homeostasis in patients and ameliorates IBD (Inflammatory Bowel Disease)-related lesions and symptoms, the anti-inflammatory mechanisms of butyrate still remain unclear. To explore the impact of butyrate on Treg (Regulatory T cell)/Th17 (T helper 17 cell) differentiation and colitis in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(146 citation statements)
references
References 31 publications
4
139
2
1
Order By: Relevance
“…In fact, USB treatment was more effective on proliferative activity (PCNA reduction) and on apoptosis induction (C‐CASP‐3 increase). Besides, although u‐A and SB alone were both able to lower iNOS and COX‐2 after 72 h treatment, in line with previously reported data, the anti‐inflammatory effects of the combination were again more pronounced. The efficacy demonstrated by USB in cancer cell lines encouraged us to verify the efficacy of the combined treatment on macroscopic ADs of Pirc rats.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, USB treatment was more effective on proliferative activity (PCNA reduction) and on apoptosis induction (C‐CASP‐3 increase). Besides, although u‐A and SB alone were both able to lower iNOS and COX‐2 after 72 h treatment, in line with previously reported data, the anti‐inflammatory effects of the combination were again more pronounced. The efficacy demonstrated by USB in cancer cell lines encouraged us to verify the efficacy of the combined treatment on macroscopic ADs of Pirc rats.…”
Section: Discussionsupporting
confidence: 90%
“…SCFAs metabolites influence T‐cell differentiation, e.g. butyrate increases T reg ‐cell percentage as well as interleukin 10 and 12 levels with the simultaneous decrease of interleukin 17 and 23 levels . Taking part in tryptophan catabolism, gastrointestinal microbiota stimulates the production of anti‐inflammatory interleukin 22, which enhances the expression of antimicrobial peptides at the mucosal surfaces .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was reported that not only neutrophils but also CD4 + T helper (Th) cells have important roles in the pathogenesis of IBD. These studies have focused on Th17 cells because the IL23/Th17/IL17A pathway is an important therapeutic target in IBD patients . However, the role of IL17A in colitis remains controversial.…”
Section: Discussionmentioning
confidence: 99%